How should normocalcemic primary hyperparathyroidism be managed? Comparison with classical hypercalcemic form (Annals of Medical Research, 2021)
Aim: Normocalcemic primary hyperparathyroidism (N-PHPT) is a different variant of primary hyperparathyroidism characterized by normal serum calcium (Ca) concentrations and elevated parathormone (PTH) levels in the absence of secondary causes of  hyperparathyroidism. However, the clinical course and therapeutic approaches of this entity have been not fully demonstrated. We aimed to determine the clinicopathological characteristics and surgical outcomes of patients with N-PHPT, comparing with patients who had hypercalcemic PHPT (H-PHPT).Materials and Methods: A total of 185 patients who underwent parathyroidectomy for PHPT were included in the study. The patients were classified as N-PHPT and H-PHPT. The two groups were then compared between each other in terms of all demographic, clinical, and surgical features.Results: One hundred and fifty-one (81.6%) patients had a diagnosis of H-PHPT while 34 (18.4%) patients were normocalcemic. Both groups were similar in age, preoperative vitamin D level, preoperative PTH level, and type of surgery (p > 0.05). Preoperative Ca level was significantly different between the groups (p < 0.01). Prevalence of urolithiasis and decreased bone density was similar between the groups (p > 0.05).Conclusion: N-PHPT patients had similar demographic and clinical features in comparison to those with H-PHPT, indicating that the surgical decision in patients with N-PHPT should be similar with H-PHPT cases.